Philosophy in Schools: A Catholic School Perspective. Issue 4 (18th March 2015) - Whittle, Sean
Abstract : This article builds on the recent Special Interest issue of this journal on 'Philosophy for Children in Transition' (2011) and the way that the debate about philosophy in schools has now shifted to whether or not it ought to be a compulsory part of the curriculum. This article puts the spotlight on Catholic schools in order to present a different argument in favour of introducing compulsory philosophy lessons into the curriculum. It is explained that in faith schools, such as Catholic ones, there is an additional need or imperative to have compulsory philosophy as part of the curriculum. This is because it serves as an effective way of avoiding the inherent dangers of confessional education, particularly the indoctrination challenge. It is argued that Catholic schools also have some intriguing theological reasons that can be used to justify the inclusion of compulsory philosophy in the school curriculum. It is proposed that when it comes to philosophy in schools there is a distinctive Catholic school perspective. As part of this it is explained why Catholic schools, perhaps more than others, need philosophy to be a compulsory part of the curriculum.